Granulation Methods Dependent Physical Characteristics of Chitosan Effervescent Granule Suspension from Mangrove Crab (Scylla serrata) Shell - Hilya Nur Imtihani; Nimas Ajeng Isbandyah; Endah Susanti; Andhika Dwi Aristyawan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The mangrove crab (Scylla serrata), a prevalent resource in coastal mangrove ecosystems, is widely utilized for consumption. Its shell offers a valuable source of chitosan, a biopolymer readily synthesized and recognized for its potential health benefits. Chitosan's unique structure, characterized by the presence of amine groups, imparts a strong positive charge, enabling it to effectively bind with negatively charged molecules such as oils and fats. This property makes chitosan a promising natural compound for managing cholesterol levels. Developing a palatable and convenient dosage form, such as an effervescent granule suspension, is crucial to enhance its public acceptance as a health supplement. This study investigated how different granulation methods (wet and dry) influence the physical properties of effervescent granules containing chitosan, both before and after reconstitution. Four distinct formulations were prepared: F1 and F2 employed dry and wet granulation, respectively, with a citric acid : tartaric acid ratio of 10% : 20%; while F3 and F4 utilized the same granulation methods but with a higher acid ratio of 13% : 26%. Comprehensive evaluation revealed that all formulations generally met quality requirements, except F3's pH (4.38 ± 0.57). Statistical analysis using an independent sample t-test indicated that the granulation method significantly affected parameters such as flow time, percentage of fines, dispersion time, and pH. Ultimately, the dry granulation method yielded the most favorable characteristics, with Formula I (F1) exhibiting superior flow properties, optimal pH, and desired viscosity.